Spatial Analysis of Landslide Potential Using Modification of the Storie In-dex Method in the Wae Batu Gajah Watershed, Ambon City, Indonesia - Abdul Muin; Heinrich Rakuasa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on data on landslide disaster events in 2022, it shows that the Wae Batu Gajah watershed is a land-slide-prone area in Ambon City. The development of increasing population settlements in this area will cer-tainly increase the risk of landslides that are getting higher and higher. Based on this, it is necessary to con-duct spatial analysis of landslide-prone areas in the Wae Batu Gajah watershed. This study aims to analyze the potential for landslides and their exposure to settlements in the Wae Batu Gajah watershed, Ambon City using the Storie Index method. The results showed that the potential for landslides in the Wae Batu Gajah watershed is a hazard class, namely not potential, low, medium, high. The high landslide potential class dom-inates the Wae Batu Gajah watershed, covering an area of 280.19 ha or 43.67% spread across the middle and upper reaches of the watershed. An area of 98.05 ha or 47.82% of the area of residential land located in land-slide-prone areas with low potential located in the lower reaches of rivers with marbles of 0-2% and 2-8% which are relatively sloping and flat. The results of the study are expected to help the Ambon City govern-ment in efforts to mitigate landslide disasters in the future and in spatial planning efforts based on disaster mitigation